PENCAPAIAN AKURASI EVALUASI BELAJAR MATEMATIKA MELALUI MEDIA APLIKASI QUIZIZ - Lili Lindasari; Yunni Arnidha (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
Mathematics is a subject that is seen by students as a difficult subject. This is due to monotonous learning, especially in the evaluation of learning, especially when learning is done online due to the covid-19 virus. Therefore, alternative learning is needed using interesting learning media. The teacher must choose one of the media applications that can be used as an evaluation tool to measure student understanding during online learning. One of the media used is the educational game Quizizz. The purpose of this study was to determine the effect of using quiz application media on the timeliness of learning mathematics. The type of research used in this study is quantitative using a quasi-experimental design with a non-quivalent control group design. The population in this study were all fifth grade students of SD Negeri Karangsari, totaling 49 students and all of them were used as samples. Data collection techniques used are test sheets and questionnaires. Data analysis using SPSS program assistance with hypothesis testing with t-test. The results showed that there was an effect of quiz media application on the evaluation of student learning in online learning, this was indicated by the significance value (p) was 0.000. Because the significance of p (0.000) < (0.05), and t-count 55.618 > t-table is 1.678, so the proposed hypothesis is accepted. The increase in students' abilities can be seen from the average score of students in the pre-test of 59.39 and in the post-test the average increases to 72.65